Highly Stable Antitumor Silver-Lipid Nanoparticles Optimized for Targeted Therapy - Darwish A; Sándor N; Szenti I; Marosvölgyi T; Juhász K; Rónavári A; Kachal E; Kutus B; Kónya Z; Balogi Z (International Journal of Nanomedicine)
Ammar Darwish,1 Nikolett Sándor,1 Imre Szenti,2 Tamás Marosvölgyi,3 Kata Juhász,1 Andrea Rónavári,2 Edi Kachal,2 Bence Kutus,4 Zoltán Kónya,2 Zsolt Balogi1 1Institute of Biochemistry and Medical Chemistry, Medical School, University of Pécs, Pécs, H-7624, Hungary; 2Department of Applied and Environmental Chemistry, University of Szeged, Szeged, H-6720, Hungary; 3Institute of Bioanalysis, Medical School, University of Pécs, Pécs, H-7624, Hungary; 4Department of Molecular and Analytical Chemistry, University of Szeged, Szeged, H-6720, HungaryCorrespondence: Zsolt Balogi, Email zsolt.balogi@aok.pte.huBackground: Silver nanoparticles (AgNPs) have a broad spectrum of biocidal effects, allowing also their antitumor application. To enhance bioavailability, minimize adverse effects and enable targeted drug delivery AgNPs may be encapsulated in liposomes. In this study we aimed to create highly stable and effective antitumor AgNP lipid formulations (LAgs).Methods: Uncapped and citrate-stabilized AgNPs were encapsulated by the lipid film hydration method using several phospholipid mixtures, followed by the essential removal of unencapsulated AgNPs by size exclusion chromatography (SEC). Purified LAgs were characterized by UV-VIS, DLS, XRD, ICP-MS, transmission electron microscopy (TEM) and glycerol-based density gradient centrifugation (DGC). Liposomal stability was assessed by carboxyfluorescein (CF) leakage, while antitumor effects of purified LAgs were tested in MTT, clonogenic and 3D spheroid invasion experiments.Results: The presence of AgNPs inside SEC-purified liposomes was confirmed by TEM, XRD and ICP-MS. Encapsulation efficiency was estimated to be between 18.7 and 25.5%. Purified LAgs had higher density as compared to free AgNPs revealed by DGC, indicating that a considerable fraction of liposomes contained AgNPs. LAgs with PC/PG, PC/PG/SM/Chol, and in particular PC/PG/SM displayed the highest stability assessed by CF leakage, whereas high content of neutral or negatively charged phospholipids was destabilizing. As shown by MTT and colony formation assays, viability and survival of A375 and RPMI-7951 melanoma cells were severely impaired by LAgs at a higher or comparable level as caused by free AgNPs. Used as a non-tumor control, HEK293 cells were less vulnerable to LAgs as compared to free AgNPs. Finally, applying the most stable lipid composition, PC/PG/SM-LAg-c, and in part PC/PG/SM-LAg-u effectively inhibited a tissue-like invasion of melanoma spheroids.Conclusion: Altogether, highly stable purified LAg formulations were created, which effectively block survival, clonogenic potential and invasion of melanoma cells, therefore could be promising NP platforms for targeted tumor therapy.Keywords: silver nanoparticle, liposome, encapsulation, tumor cell viability, tumor spheroid invasion